Analisa Pembelajaran Responsif Disleksia Film "Taare Zameen Par" dan Relevansinya dengan PAUD - Sania Fildza Fatin Najah Sania; Fitrotul Hikmah Fitroh (Early Stage, 2026)
This study aims to analyze dyslexia-responsive learning strategies in the film Taare Zameen Parand their relevance to Early Childhood Education (ECE). The method employed is qualitativewith a content analysis approach. Data comprising dialogue fragments, gestures, andpedagogical actions were collected through structured audiovisual observation techniques andsubsequently analyzed using an interactive model. The results indicate that the character Ishaanrepresents the characteristics of developmental dyslexia, specifically visual-orthographiccognitive impairments, where a lack of environmental literacy triggers stigmatization andnegative psychosocial impacts. To address these challenges, the responsive learning strategiesinitiated by Teacher Nikumbh implement an individualized approach, emotional support,parental collaboration, and a multisensory method using concrete media. This interventionstrategy holds strong methodological relevance to ECE principles that emphasize child-centeredlearning and learning through play during the golden age phase. From the perspective of Islamiceducation, this responsive approach serves as a tangible implementation for guiding andoptimizing children's unique innate potential (fitrah) from an early age without negativelabeling